Risk Management in Chinese SMEs: Factors Influencing SME's Risk Management and Perception of Risk-Managing Instruments - Weng, Weng (2011)
Since the concept of risk was introduced into the contemporary business world, where almost every decision is quantified in financial terms, its importance has been increasingly recognized by organizations. In order to retain the optimal amount of risk while reduce the probability of undesirable outcomes, a variety of methods and standards have been developed. However, most of these established risk management frameworks are designed for relatively large companies rather than Small and medium-sized enterprises (SMEs), which are actually more vulnerable to both financial and non-financial risks due to constrained funding options and limited ability to attract and retain professional personnel. As there was not so much research concerning factors influencing SMEs’ risk management in China, this research is interested in examining the influences of company and owner-managers’ background factors on Chinese SMEs’ formal risk-managing activities (risk assessment and business plan). In addition, Chinese SMEs’ perceptions towards three main instruments of risk management (risk assessment, business plan and insurance) will also be analyzed. Consistent correlations were found between three independent variables and the two formal risk-managing activities: 1) companies with relatively small business scales have more incentives to have formal risk-managing activities; 2) non-owners were proved to be more willing to have risk assessments and business plans than owner; 3) owner-managers in the oldest age group are less likely to have formal risk management activities. Besides, four variables were proved to have significant correlations with one of the risk management practices: 1) SMEs with a history of 4 to 10 years tend to have written business plans; 2) firms in “moderate to high growth market” were found to be less likely to have risk assessments; 3) male owner-managers were less likely to be business planners; 4) owner-managers who have participated in extra non-degree-based educational programs were confirmed to be less likely to have business plans. In the analysis of the three risk-managing instruments, the result confirmed that more SMEs have well written business plans than formal risk assessments. However, the difference between these two instruments is quite small. According to the test result of interaction effects between “having a risk assessment” and “having a business plan” on ratings for the importance of insurance, firms with neither business plans nor risk assessments place insurance in a more essential place. However, the ratings by firms with both business plans and risk assessments are not significantly higher than the average level.